Management Audit of the Effectiveness of Human Resources in Government Organizations - Supardi, Supardi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
Human resources (HR) effectiveness is an essential factor in the success of an organization, especially in a government environment that influences the delivery of public services. This research aims to evaluate the effectiveness of human resources (HR) in government organizations through a management audit approach. This research uses a qualitative approach with descriptive methods. The research results show that management audits in improving the effectiveness of human resources (HR) in government organizations include several essential steps. This includes HR planning by considering SWOT analysis, HR recruitment and selection by ensuring compliance with SOPs and statutory regulations, employee training and development to increase competency, performance appraisal to encourage productivity, and management of compensation and labor protection that is fair and by regulations. Audits are also crucial in ensuring that layoffs and retirements are carried out transparently and with due regard for workers' rights. Furthermore, management audits of human resources (HR) effectiveness bring various benefits to the organization. Audits help identify weaknesses in HR management, enable focus on necessary improvements, and increase the efficiency of HR processes. In addition, audits ensure legal compliance with HR policies, reduce legal risks, and enable employee development that aligns with organizational needs. Thus, HR management audits ensure optimal performance and organizational sustainability